Effects of training on postural control and agility when wearing socks of different compression levels - Jaakkola Timo (Biomedical Human Kinetics, 2017)
Study aim: The aim of this study was to evaluate the effects of training while wearing socks differing in compression level (clinical, sub-clinical, regular) on performance of static and dynamic balancing and agility tasks in healthy, physically active people. We sought to understand whether socks with different compression properties supported postural regulation and agility task performance by enhancing somatosensory perception, unskewed by specific age range effects. Material and methods: Participants comprised 61 adults aged 18-75 years, divided into three groups (two experimental groups wearing clinical or sub-clinical level compression socks, and one control group wearing regular non-compression socks during training). An 8-week (2 × 1h per week) intervention programme was administered to train static and dynamic balance and postural control, leg strength and agility. Results: A mixed model ANOVA revealed no differences in static and dynamic balance and postural control and agility performance between clinical, sub-clinical, and control groups before and after training. All groups significantly improved their test performance, suggesting that training had some benefit on motor performance. Conclusions: These results raised interesting questions requiring further investigation to examine the effects of wearing socks (with and without different levels of compression) on motor behaviours in specific groups of elderly vs. young participants, in physically active vs. less physically active people, and in performance settings outside standardized laboratory tests to study applications in natural performance environments.